L. MOHOLY-NAGY - Vision in Motion - Juárez Chicote, Antonio (ZARCH, 2019)
László Moholy-Nagy Vision in Motion Chicago: Paul Theobald & Co, 1947. 371 páginas. Tapa dura. Idioma: inglés. 45 €. ISBN-10: 9780911498004; ISBN-13: 978-0911498004